The Ceramic legacy of Anna O. Shepard - Bishop, Ronald L.; Lange, Frederick W. 1944- (University Press of Colorado, 1991)
"Revised papers from a 1988 conference on the history of ceramic technology in archaeology. Part I examines Shepard's research, covering her contributions to Mesoamerican archaeology. Part II deals with current issues, including a discussion of Mesoamerican Plumbate Ware. Part III concludes with an assessment. In addition to valuable historical analysis, important theoretical and methodological issues are addressed"--Handbook of Latin American Studies, v. 57.